Toward a Euro-Islamic Model of Halal Economic Integration: The Case of Bulgaria - Daniel Petrov (Journal of Islamic Economics and Business, 2026)
The rapid expansion of the global halal economy has created new opportunities for non-Muslim countries to participate in halal value chains. However, limited evidence exists regarding the institutional readiness and development potential of the halal industry in emerging European economies. This study examines the economic, institutional, and socio-cultural factors influencing halal industry development in Bulgaria. A mixed-method approach was employed, combining regulatory analysis, documentary analysis, SWOT analysis, and a nationwide survey involving 236 stakeholders. The findings indicate that Bulgaria possesses moderate institutional readiness for halal industry development. Economic potential and regulatory compatibility represent key strengths, while fragmented institutional coordination, the absence of a nationally recognized halal certification system, and limited institutional trust remain significant constraints. Regression analysis identifies economic potential as the strongest determinant of stakeholder willingness to support halal industry development, followed by institutional trust and socio-cultural acceptance. The findings suggest that Bulgaria has favorable conditions to strengthen its position in the regional halal economy, provided that certification governance, institutional coordination, and public awareness are further improved. These findings provide the basis for a Euro-Islamic Model of Halal Economic Integration, demonstrating how economic competitiveness, institutional credibility, and socio-cultural legitimacy jointly facilitate halal market development within a secular European institutional environment.